The role of nocturnal sleep on the retention, adaptability, and relearning rate of a motor skill - Fernanda Yngrid Martins Sousa; Yasmin de Melo Rocha e Silva; Ana Kariele da Silva Santos; Gisele Carla dos Santos Palma; Renata Louise Ferreira Lemos; Giordano Marcio Gatinho Bonuzzi (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: The influence of sleep on the adaptability and relearning rate during learning of complex motor skills is still unknown, limiting the comprehension of the sleep role in motor memory consolidation. Thus, we aimed to investigate the nocturnal sleep influence on retention, adaptability, and relearning rate of the dart-throwing task. Methods: Sixty healthy adults were divided into two groups: SLEEP and WAKE. Both groups practiced an under-arm dart-throwing task. However, WAKE practiced in the morning and performed a retention phase in the evening, and SLEEP practiced in the evening and performed a retention phase in the morning of the next day. The practice and retention phases were separated by 12 h in both groups. There were analyses regarding retention (retention test), adaptability (delayed transfer test), and relearning rate (savings). Results: Both groups improved their performance across the acquisition phase and maintained it in the retention test. The groups did not demonstrate adaptability and did not demonstrate a significant difference in relearning rate. Conclusion: We conclude that nocturnal sleep did not modulate the consolidation of motor memories related to ballistic discrete motor skills.